MORPHOLOGICAL AND HISTOCHEMISTRY RESEARCHES OF ORGANS OF WARM-BLOODED UNDER INFLUENCE Of DETERGENTS - Щербань, М.Г. (World of Medicine and Biology, 2012)
With the purpose of hygienical regulation in water of reservoirs of group of chemical pollutants of sources of water-supply in the process of sanitary-toxicological experiments on white rats morphological and histochemistry researches of organs of experimental animals are executed. The educed changes reflected functional tension that in part of structural-functional units resulted in дистрофическим and destructive changes in organs warm-blooded. The most expressed changes are marked in a liver and buds, especially, in the structure of epithelium of tubulis. The expressed violations were observed in a spleen. The specific of action and degree of toxicness of substances showed up in direct dependence on the dose of influence.
Keywords: chemicals; white rats; experiment; morphological